Study on productivity of office workers and power consumption of air conditioners in a mixed-mode ventilation building during springtime. (15th April 2022) - Arata, Shiro; Kawakubo, Shun
Abstract: The thermal environment in offices affects the productivity of workers; thus, it is important to adjust the thermal environment appropriately with heating, ventilation, and air conditioning. However, there is an urgent need to reduce the amount of energy used in the building sector for cooling, which has been rising. Mixed-mode ventilation has attracted attention as a means of decreasing air conditioning power consumption and improving the satisfaction of office workers. In the present study, a measurement survey and a questionnaire survey were conducted during springtime to investigate air conditioning power consumption during mixed-mode ventilation and to elucidate the relationship between the use of mixed-mode ventilation and productivity. The power consumption on the mixed-mode ventilation floors was less than that on the mechanical ventilation floors in the measurement period when the average outdoor air temperature was 21 °C, with savings ranging from 3.1% to 70.6%, although it varied widely with the weather conditions. The relationship between the use of mixed-mode ventilation and productivity was analyzed using multilevel analysis (hierarchical linear model), a method that considers the data hierarchy. Mixed-mode ventilation improved the productivity of male participants by about 9.1%, suggesting that mixed-mode ventilation could both decrease air conditioning power consumption and improve productivity during springtime. However, the increase in productivity of female participants was about 0.5%, indicating that there may be differences depending on gender. The present study has practical implications for promoting mixed-mode ventilation as a means to reduce air conditioning power consumption in offices and improve productivity. Highlights: Mixed-mode ventilation in springtime was studied by measurements and questionnaire. The effects of mixed-mode ventilation were analyzed by multilevel analysis. Mixed-mode ventilation reduced air conditioner power consumption by 3.1%–70.6%. Mixed-mode ventilation improved productivity by about 9.1% in male participants. The effects of mixed-mode ventilation on productivity may differ by gender.